T. Wilder's Play “Our Town” in the Context of A. Chekhov's Dramaturgy - Valentyna Borbuniuk (Pitannâ Lìteraturoznavstva)
The research is connected with a new approach to understanding the poetics of T. Wilder's play “Our Town” (1938). The comparative and intertextual methods of research are applied. This methodological approach made it possible to determine the semantic orientations of the artistic world of T. Wilder, to trace the features of Chekhov's aesthetic principles reflection in his play. The scientific novelty of the work is determined by the absence of dramatic heritage of T. Wilder in the context of Chekhov's works in contemporary literary criticism of studies. The chosen scientific approach testifies that the development/assimilation of the experience of Chekhov's dramaturgy by the American playwright was promoted by the ability of Chekhov's poetics to vary and to exist in various contexts. A distinctive feature of the play “Our Town” is its dialogic attitude to Chekhov's plays, which affected, first of all, the space-time organization of the text. The comprehension of the poetics of T. Wilder's play “Our Town” through the prism of Chekhov's dramatic art fills the lacuna that existed until recently in literary criticism. Chekhov's motifs, organically entering the art of “Our Town”, expand its semantic horizons. Despite his own interpretation of Chekhov's artistic principles, the depiction of life and human in T. Wilder's play is Chekhov's fundamentally every day and non-heroic thing, and the whole system of pictorial means is aimed at the construction of ordinary events to universal and general philosophical level.